Urbanization and Its Impact in Contemporary China - Li, Peilin; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This book addresses a wide range of social issues in connection with urbanization, which is providing new momentum for China's economic restructuring and social progress, including the educational gap; the middle class in urbanization; consumption; division of labor; and social integration. All chapters are based on updated nation-wide sampling survey data. Taken together, they provide a lens for understanding various aspects of urbanization and its impacts on China's economy and society.
Urbanization and Stage of New Growth of China -- General State of Urbanization and People's Livelihood -- Consumption State and Consuming Characters of Urban and Rural Residents -- Labor Market Segmentation in Process of Urbanization -- Urbanization and Social Integration of Migrant Workers -- Increase of Education Chance and Urban Education Inequality -- Urbanization and Growth of Middle Class -- Discovery from Research and Related Suggestions.
Keywords: Sociology, Urban; Human geography; Urban Sociology; Human Geography